Rankings of Canadian Universities, 2000: Buyer Beware - Page, Stewart; Cramer, Ken (Canadian Journal of Education/Revue canadienne de l’éducation, 2000)
We present a critical perspective on the rankings of Canadian universities pre- sented in Maclean's magazine, November 20, 2000. Data from several statistical analyses, including cluster analysis, show that in many cases universities actually resemble each other in a manner different from their classification or final ranking by Maclean's, and that the magazine’s classifications are often decided by variables not realistically measurable by or amenable to students. We summarize several pitfalls in the ranking procedures for the 2000 data, and in ranking exercises more generally. In their present form, Maclean's data cannot be logically or empirically useful to students. Les auteurs critiquent le classement des universités canadiennes présenté dans le Maclean's le 20 novembre 2000. Les données tirées de plusieurs analyses statistiques, dont l’analyse typologique, indiquent que, dans bien des cas, les universités se res- semblent sur d’autres fronts que ce que laisse supposer leur position dans le pal- marès. Les auteurs résument les écueils méthodologiques liés au classement pour les données de 2000. Dans leur forme actuelle, les classifications du magazine reposent sur des variables qui ne sont ni empiriquement mesurables ni accessibles aux étudiants.